Guidelines for evaluating water in pit slope stability - Read, John Russell Lee, 1939-; Beale, Geoff (CSIRO Publishing, 2013)
Guidelines for Evaluating Water in Pit Slope Stability is a comprehensive account of the hydrogeological procedures that should be followed when performing open pit slope stability design studies. Created as an outcome of the Large Open Pit (LOP) project, an international research and technology transfer project on the stability of rock slopes in open pit mines, this book expands on the hydrogeological model chapter in the LOP project's previous book Guidelines for Open Pit Slope Design (Read & Stacey, 2009; CSIRO Publishing). The book comprises six sections which outline the latest technology and best practice procedures for hydrogeological investigations. The sections cover: the framework used to assess the effect of water in slope stability; how water pressures are measured and tested in the field; how a conceptual hydrogeological model is prepared; how water pressures are modelled numerically; how slope depressurisation systems are implemented; and how the performance of a slope depressurisation program is monitored and reconciled with the design. Guidelines for Evaluating Water in Pit Slope Stability offers slope design practitioners a road map that will help them decide how to investigate and treat water pressures in pit slopes. It provides guidance and essential information for mining and civil engineers, geotechnical engineers, engineering geologists and hydrogeologists involved in the investigation, design and construction of stable rock slopes.